2013
DOI: 10.1026/0012-1924/a000089
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung und Validierung einer ultrakurzen Operationalisierung des Konstrukts Optimismus-Pessimismus

Abstract: Das Konstrukt Optimismus-Pessimismus ist aufgrund seiner vielfältigen Beziehungen zu gesellschaftlich relevanten Prozessen und Phänomen nicht nur für Psychologen, sondern auch für Forscher anderer Disziplinen von Interesse, zum Beispiel für Sozialwissenschaftler, Ökonomen und Gesundheitsforscher. In deren Untersuchungen sind aufgrund starker monetärer Restriktionen insbesondere ökonomische Operationalisierungen gefragt. Auf der Grundlage der weit verbreiteten Konstruktdefintion von Scheier und Carver (1985) , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 36 publications
5
59
0
2
Order By: Relevance
“…On a 7-point Likert scale (e.g., 1 = not at all optimistic ; 7 = very optimistic ), participants indicate how optimistic or pessimistic they are in general (e.g., “How optimistic are you in general?”). For the SOP2, acceptable to good internal consistency was demonstrated (ω = .74–.83; α = .78–.99) and significant correlations were shown with life satisfaction, self-efficacy, or another optimism measure ( Kemper, Wassermann, Hoppe, Beierlein, & Rammstedt, 2017 ; Kemper et al, 2012 ). Kemper et al (2012) found a general factor model with two group factors for optimism and pessimism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a 7-point Likert scale (e.g., 1 = not at all optimistic ; 7 = very optimistic ), participants indicate how optimistic or pessimistic they are in general (e.g., “How optimistic are you in general?”). For the SOP2, acceptable to good internal consistency was demonstrated (ω = .74–.83; α = .78–.99) and significant correlations were shown with life satisfaction, self-efficacy, or another optimism measure ( Kemper, Wassermann, Hoppe, Beierlein, & Rammstedt, 2017 ; Kemper et al, 2012 ). Kemper et al (2012) found a general factor model with two group factors for optimism and pessimism.…”
Section: Methodsmentioning
confidence: 99%
“…For the SOP2, acceptable to good internal consistency was demonstrated (ω = .74–.83; α = .78–.99) and significant correlations were shown with life satisfaction, self-efficacy, or another optimism measure ( Kemper, Wassermann, Hoppe, Beierlein, & Rammstedt, 2017 ; Kemper et al, 2012 ). Kemper et al (2012) found a general factor model with two group factors for optimism and pessimism. The item pessimism was recoded to calculate the mean (range: 1–7).…”
Section: Methodsmentioning
confidence: 99%
“…Die Skala Optimismus-Pessimismus-2 (SOP-2) [25,26] diente der Erfassung der Persönlichkeitsdisposition Optimismus. Die bei den likertskalierten Items der Skala (Optimismus, Pessimismus) können nach Umkodierung zu einem Gesamtwert für Optimismus summiert werden.…”
Section: Introductionunclassified
“…The personality trait optimisim/pessimism will be assessed with the scale Optimism-Pessimism-2 (SOP2). The SOP2 has been validated among the general population and has shown good reliability and validity ( 96 ).…”
Section: Materials and Equipmentmentioning
confidence: 99%